Investigating the desperate housewives: Using gender-role attitudes to explain women's employment decision in twenty-three European countries - Jerome De Henau (The Open University, Economics Department, 2007)
This paper analyses the impact of a set of gender-role attitudes on the labour market situation of women with and without young children. These attitudes are used as a proxy for stated preferences. Our study covers 23 European countries, using an original up-to-date micro data-set, the European Social Survey (round 2004), completed with regional and national information on the institutional and socio-economic context. In particular, we investigate whether the effect of the presence of young children and the effect of attitudes towards female employment and maternal roles are substitutes, complementary or multiplicative, using interaction variables. We use a multinomial logit regression model to account for three different employment statuses as dependent variable, full-time, part-time and not in employment. Results show substantial cross-country differences in the influence of attitudes on work, which differs by level of education, but not according to the presence of young children. However, the negative effect of young children on the full-time employment of mothers is stronger than the positive effect of egalitarian attitudes in countries with lower subsidised childcare provision. These results refine the discussion on the effect of work/life balance policies in Europe.
Keywords: C43; J13; J21; 330; gender-role attitudes; social policies; dual-earner couples; labour market participation; part-time work; parenthood; Weibliche Arbeitskräfte; Soziale Rolle; Soziale Norm; Geschlecht; Kinderbetreuung; Teilzeitarbeit; Familie-Beruf; Sozialpolitik; Sozialstaat; Europa